Amidos oxidados e modificados com ácido cítrico: obtenção e aplicação como agentes clarificadores do mosto cervejeiro - Arita, Daniela Hirata (2019)
In the brewing process it is common to use clarifying agents in order to reduce colloidal particles and to obtain a clear and bright product. The clarifiers may be applied to hot wort, fermented beer and/ or maturation. Carrageenan gum, a polymer with anionic characteristics,is an example of a clarifying agent applied in the final boiling step to increase sedimentation and compaction of the protein-polyphenol complex and thereby minimize turbidity in beer. This clarification results from electrostatic interactions between thenegative charges of the carrageenan molecule and the positively charged proteins. Modification of starches is an alternative to overcome limitations of native starches and to increase their usefulness in industrial applications. The present study aims to obtain anionic starches by oxidationwith sodium hypochloriteand esterification processes with citric acid, from corn, cassava and potato starches, to be later evaluated as potential beer clarifiers. The double modification (oxidation and esterification) is also proposed as an alternative to increase the negative charge of the polymer, hoping to obtain a better clarification effect. The characterization of the modified starches was performed by analysis of swelling powerandsolubility, infrared spectroscopy (FTIR), scanning electron microscopy (SEM), intrinsic viscosity, amylose content, determination of esterification percentage and carboxyl group content, X-ray diffractometry (XRD), thermal (DSC) and paste properties(RVA). These analysis showed the obtaining of dextrins in the samples esterifiedwith citric acid, as well as the obtaining of anionic starches for all the chemical modifications made. However, for treatedstarches with citric acid, two types of products are possible: monoesterified or diesterified (cross-linked), whose differences in chemical structures appear to interfere with the clarification power of beers, as shown by the results of clarity and quantification of proteins and compounds phenolics performed during the brewing stages. The only citric acid treated samples presented the best results in the beer analysis, as opposed to doubly modified starches, indicating a possible cross-linking reaction. The dextrinized potato starch with citric acid (BaDC) was the one that presented clarifying power closer to the carrageenan. In addition, it wasalsoverified that the efficiency of the modified starchesin this studyoccurs mainly during the maturation, different from the gum carrageenan that starts the clarificationin the final stage of boiling.